A DECADE OF PROBIOTIC AQUACULTURE PRACTICE: BIBLIOMETRIC INSIGHTS INTO TRENDS, PLAYERS, AND EMERGING TOPICS - Rashidah Abdul Razak; Muhammad Fitri Yusof; Syamsul Ahmad Ariffin; Muhamad Zudaidy Jaapar; Amatul Samahah Md Ali (Indonesian Aquaculture Journal, 2026)
Probiotics in aquaculture gain research interest due to their potential to improve production and promote sustainable aquaculture. This study aims to systematically identify the trend, topic of interest, key players and collaboration in probiotic aquaculture research field for past 10 years. We conducted a bibliometric analysis using Scopus to collect and analyse scholarly publications related to probiotic in aquaculture. The sample is composed by 1467 articles in total with increase trends pattern in number of publications per year. Metrics such as citation counts, co-authorship networks, and keyword co-occurrence were employed to unveil the research landscape. The VOSviewer tool was utilized for network visualizations, offering insights into collaboration patterns and thematic clusters. Preliminary findings indicate increasing trend in terms of documents per year, with countries such as China, India, Spain and US playing pivotal roles in number of publications. Keyword co-occurrence analysis uncovers central themes is probiotic and aquaculture, while emerging topics such as intestinal health, Penaeus vannamei, bacteria, and water quality start to be explored. Citation analysis discovers most contributing authors, countries, institution, and journals in this research area. The co-authorship network analysis reveals clustering of collaborations between countries, emphasizing the global interest research of probiotic in aquaculture. We concluded that global theme will remain the major focus with new collaborations focus on specific niche in this research will emerge as it benefits the contributing countries.